5V-class sulfurized spinel cathode stable in sulfide all-solid-state batteries. (December 2021) - Wang, Yue; Lv, Yan; Su, Yibo; Chen, Liquan; Li, Hong; Wu, Fan
Abstract: Sulfide all-solid-state lithium-ion batteries represent one of the most promising energy storage technologies duo to higher safety and ionic conductivities. To further improve its energy density and application, high-voltage LiNi0.5 Mn1.5 O4 (LNMO) spinel cathode is highly desirable due to its high energy density, low cost, environmental friendliness and Co-free nature. However, sulfide solid electrolyte is not compatible with LNMO cathode, for which issue the reported solutions majorly focus on surface coating. In this work, we propose an efficient approach to sulfurize LNMO itself for an essentially new LNMOS cathode, which not only suppresses interfacial side-reactions but also improve ionic/electronic conductivity of the cathode. This method ultimately improves the interfacial compatibility and consequently the LNMOS/sulfide all-solid-state-battery performances, including 3 times higher initial discharge capacity and much better reversible cycling stability. Detailed analyses on the interface are performed for in-depth understanding and further development of high-energy-density sulfide all-solid-state batteries using 5V-class spinel cathodes. Graphical Abstract: In this work, we propose an efficient approach to sulfurize LiNi0.5 Mn1.5 O4 itself for an essentially new LiNi0.5 Mn1.5 O4 -Sx cathode, which ultimately solves the interfacial incompatibility issue between high-voltage cathode materials and sulfide solid electrolyte. Compared with the previously reported surface coating approach, our bulk doping strategy improves the initial discharge capacity of all-solid-state batteries by 3 times, leading to a 6-times longer cycle life and a 1.3-times higher capacity retention rate after 10 cycles by ultimately improving the compatibility between 5V-class cathode and sulfides. ga1 Highlights: Realization of 5V-class cathode stable in sulfide all-solid-state batteries. Improved compatibility between 5V-class cathode and sulfide solid electrolytes. New type of spinel cathode with bulk doping by a facile solid-state synthesis method. 3-times higher initial discharge capacity. 6-times longer cycle life and 1.3-times higher capacity retention rate after 10 cycles.